2005
DOI: 10.1017/s0004972700035073
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the isometric composition operators on the Bloch space

Abstract: In this paper, we characterise the analytic functions

-¥ f o

Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Then ψ = ϕ • L α is an analytic function of ∆ into itself such that ψ(0) = 0 and β ψ = 1. As mentioned above, by Theorem 5 of[8], C ψ preserves the Bloch norm, i.e. f • ψ = f for all f ∈ B.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Then ψ = ϕ • L α is an analytic function of ∆ into itself such that ψ(0) = 0 and β ψ = 1. As mentioned above, by Theorem 5 of[8], C ψ preserves the Bloch norm, i.e. f • ψ = f for all f ∈ B.…”
mentioning
confidence: 82%
“…In Theorem 5 of [8], the second author proved that every analytic function ϕ of ∆ into itself mapping 0 to 0 and having Bloch norm equal to one induces an isometric composition operator on the Bloch space.…”
Section: One-point Sets Of Bloch and Normal Functions 521mentioning
confidence: 99%
See 1 more Smart Citation
“…In [10] and [2], it was shown that there is a large class of isometric composition operators on the Bloch space of the disk and more generally on bounded homogeneous domains that have the disk as a factor. We shall now prove that there are no isometries among the composition operators between the Hardy space H ∞ and the Bloch space of the disk.…”
Section: Ieotmentioning
confidence: 99%
“…In [3] The isometric composition operators on the Bloch spaces in the unit disk were discussed by Martín and Vukotić [7], Colonna [8], Allen and Colonna [9,10], Li and Zhou [11]. The same problems were studied on the Bloch spaces in the unit polydisk by Cohen and Colonna [12], in unit ball by Li [13], and Li and Ruan [14].…”
Section: Introductionmentioning
confidence: 99%